Comparison of the Performance of Three Blood Culture Systems in a Chinese Tertiary-Care Hospital - Li, Guanlin; Sun, Jingjing; Pan, Shoucheng; Li, Wenti; Zhang, Shijie; Wang, Yongfeng; Sun, Xiaoxu; Xu, Hui; Ming, Liang (Frontiers in Cellular and Infection Microbiology, 2019)
In this study, we evaluated the performance of three blood culture systems in a Chinese tertiary-care hospital. Samples of simulated bacteremia were prepared using 10 mL of fresh blood from healthy humans and bacterial suspensions of known cell density. Portions of the specimens were treated with an antibiotic or antifungal drug at specified concentrations to simulate antibacterial drug treatment. We analyzed three blood culture systems: BACTEC Plus, BacT/Alert, and VersaTREK. Both time-to-detection (TTD) of 10 types of bacteria and five types of yeasts in samples without antibiotic treatment and positive detection rate of samples treated with different concentrations of antibiotic or antifungal drugs were compared among the culture systems. We also retrospectively analyzed the use of the culture systems in our hospital from 2015 to 2018. In the simulated study, in the absence of antibiotics, the VersaTREK REDOX 1 displayed the shortest TTD for Pseudomonas aeruginosa, Haemophilus influenzae, Staphylococcus aureus, Streptococcus pneumoniae, Candida albicans, and Candida glabrata (P < 0.001). Among the anaerobically cultured samples, BACTEC lytic/10 anaerobic/F displayed the shortest TTD for Escherichia coli, S. aureus, Enterococcus faecalis, S. pneumoniae, Bacteroides fragilis, and Bacteroides vulgatus (P < 0.001). Comparatively, BacT/Alert FA/FN showed no advantages. In antibiotic-treated samples, overall recovery rates for the BACTEC, BacT/Alert, and VersaTREK systems were, were 70.2%, 43.7%, and 27.4%, respectively. BACTEC facilitated higher recovery rate than the other two systems (P < 0.001). In antifungal treatment, the overall recovery rates for the BACTEC, BacT/Alert, and VersaTREK systems were 93.9%, 98.3%, and 69.4%, respectively. BACTEC Plus showed a recovery rate comparable to that of BacT/Alert (P = 0.835), and the recovery rate of both these systems was higher than that of VersaTREK (P < 0.001). The TTD values and positive rates determined in the retrospective study were consistent with those obtained in the simulated study. The combination of BACTEC PLUS Aerobic/F and BACTEC lytic/10 anaerobic/F culture systems displayed the best clinical performance. Furthermore, the BacT/Alert FAN culture system was found to be more resistant to antifungal drugs and levofloxacin, whereas the VersaTREK system is considered more suitable for primary blood cultures without antibiotic supplementation.